The Local Roots of Corporate Social Responsibility - Attig, Najah (Journal of business ethics, 2017)
We provide new evidence that the prosocial attitudes of local residents play a significant role in determining a firm’s corporate social responsibility (CSR) engagement. We show that firms are more likely to engage in CSR initiatives when they are headquartered in areas with large senior citizen populations and where a large fraction of the population makes charitable donations. In contrast, we find that firms are less likely to engage in CSR initiatives when they are headquartered in areas with large religiously affiliated groups. After establishing the local demographic roots of CSR demand, we then examine the relationship between the firm’s CSR activities and its market valuation. Our results suggest that CSR initiatives create value when they are properly aligned with local residents’ prosocial attitudes. Overall, our study stresses the role of local residents’ CSR preferences in mediating the relationship between CSR and market valuations.